2013
DOI: 10.1007/s00410-013-0899-9
|View full text |Cite|
|
Sign up to set email alerts
|

Melts of garnet lherzolite: experiments, models and comparison to melts of pyroxenite and carbonated lherzolite

Abstract: Phase equilibrium experiments on a compositionally modified olivine leucitite from the Tibetan plateau have been carried out from 2.2 to 2.8 GPa and 1380 to 1480 °C. The experiments produced liquids multiply saturated with spinel and garnet lherzolite phase assemblages (olivine, orthopyroxene, clinopyroxene and spinel +/-garnet) under nominally anhydrous conditions. These SiO 2-undersaturated liquids and published experimental data are utilized to develop a predictive model for garnet lherzolite melting of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 71 publications
3
59
0
Order By: Relevance
“…In the Ol-Cpx-Qz diagram, they plot at normative Cpx values lower than the multiple saturation points and near the ~14 kb Ol + Opx saturation boundary (cf. Grove et al 2013) (Fig. 13b).…”
Section: The Deccan Primary Magmasmentioning
confidence: 86%
See 2 more Smart Citations
“…In the Ol-Cpx-Qz diagram, they plot at normative Cpx values lower than the multiple saturation points and near the ~14 kb Ol + Opx saturation boundary (cf. Grove et al 2013) (Fig. 13b).…”
Section: The Deccan Primary Magmasmentioning
confidence: 86%
“…13b). Grove et al (2013) conclude that such characteristics may indicate melting of a non-lherzolitic mantle source such as olivine pyroxenite, and Melluso et al (1995) in fact inferred a clinopyroxene-rich source for the Saurashtra high-Ti picrites. Therefore, although the data show a large scatter in Fig.…”
Section: The Deccan Primary Magmasmentioning
confidence: 94%
See 1 more Smart Citation
“…The latter, they conceded, may well result from an admixture of recycled oceanic crust, but that after mixing the result was merely fertile peridotite. Comparing Hawaiian basalt compositions to a model derived from their phase equilibrium experiments, Grove et al (2013) found that "Magmas with major element compositional characteristics of pyroxenite melts are truly the rare exception in Hawaii, and only 3 emerge from this analysis of major element characteristics." They had, however, not considered nickel or other transition metals, which form some of the strongest evidence of a non-peridotite component, and concluded that, "From this major element evidence, it appears that we must identify processes that can reconcile both the major and trace element signatures of Hawaiian lavas."…”
Section: Lithologic Heterogeneitymentioning
confidence: 99%
“…As the xenoliths provide minimum pressure bounds (Chin et al 2012), they clearly were formed within the garnet peridotite field (Fig. 18), and as La Posta plutons have REE patterns of residual garnet (Gromet and Silver 1987), it is reasonable to assume that the slab failure basalt magma originated from rising asthenosphere at deeper levels, say in the garnet stability field (Grove et al 2013), than the precursors to typical arc magmas, which appear to be formed at shallower levels by melting in the plagioclase and spinel stability fields (Till et al 2012).…”
mentioning
confidence: 99%